Blended Project-Based Learning Model in Developing Students' Soft Skills in Higher Education Setting - Rukminingsih; Munawaroh; Wiwin Sri Hidayati; Diah Puji Nali Brata (Proceeding International Conference on Digital Education and Social Science, 2024)
This study explores the use of Blended Project-Based Learning (Blended PBL) in higher education to enhance students' soft skills and fulfil higher education curriculum requirements involves integrating technology with traditional project-based learning method. This qualitative research involves students from the Fifth semester Study Programs at the Faculty of Teacher Training. Education, Private University in Jombang. The object of research is to portray the improvement of students' soft skills through blended PBL in order to prepare future professional and personal success. The data collection used open-ended questionnaire and observation. The validity of the data uses method triangulation, source triangulation, and perseverance of observation. The data was analyzed by thematic analysis. The findings showed that blended PBL Model in education can enhance students' soft skills which include aspects of self-awareness, trust, adaptability, critical thinking, organizational awareness, attitude, initiative, empathy, integrity, self-control, leadership, problem-solving, risk-taking, and Time management. The Blended Project-Based Learning (Blended PBL) model in higher education combines technology and traditional methods, involving real-world projects, critical thinking, and collaboration. Based on these findings, it is suggested for the educators in higher education institutions can effectively implement a Blended PBL model that not only enhances academic learning but also develops essential soft skills, preparing students for future professional and personal success.